2006
DOI: 10.1158/1535-7163.mct-06-0043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an epidermal growth factor receptor tyrosine kinase inhibitor on actin remodeling in anin vitrobladder cancer carcinogenesis model

Abstract: Alteration of actin remodeling is a marker of malignantassociated field defect and a potential surrogate biomarker for chemoprevention trials. We tested erlotinib, a specific tyrosine kinase inhibitor of epidermal growth factor receptor (EGFR), on actin remodeling in a bladder carcinogenic model consisting of untransformed HUC-PC cells and transformed MC-T11 cells, both derived from the same normal human urothelial clone immortalized by SV40. Erlotinib had a selective growth inhibitory and actin remodeling eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…3 C). Consistent with published results 27 the estimated IC 50 value is in the order of 5 µmol/L. Thus, erlotinib inhibits migration more efficiently than it prevents an increase of the cell number.…”
Section: Resultssupporting
confidence: 88%
“…3 C). Consistent with published results 27 the estimated IC 50 value is in the order of 5 µmol/L. Thus, erlotinib inhibits migration more efficiently than it prevents an increase of the cell number.…”
Section: Resultssupporting
confidence: 88%
“…Previous research has focused on an anti-metastasis effect from one of these pathways, but not from both. As a consequence, while it was possible to discover the reduction in EMT from one of the EGFR downstream signaling pathways, the effect of the other pathway was unclear (33)(34)(35); on the other hand, in this study we found that TJE treatment led to a decrease in EGF-induced EMT though blocking of both pathways. TJE had a similar effect to the use of the inhibitors PD 98059 for Erk inhibition and LY 294002 for Akt inhibition (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…The EGFR is an actin-binding protein 54 which has been shown to reorganize the junctional actin cytoskeleton 55 . PI3K can also disrupt the actin cytoskeleton 56 , while both contribute to actin filament remodelling throughout the cell 57,58 . EGFR is also highly connected to the functioning of the Golgi apparatus in protein transport 59,60 and is a plasma membrane receptor.…”
Section: Discussionmentioning
confidence: 99%